Preoperative conjunctival flora and antibiotic susceptibility in cataract surgery patients at Ibn Al-Haitham teaching eye hospital in Baghdad, Iraq - Mohammed A. Fenjan; Furkaan Majied Hamied; Ahmed Sermed Al Sakini; Hamzeh Khorsheed; Sandra Thair Al-aish (Journal of Ophthalmic Inflammation and Infection)
Abstract Background Endophthalmitis is a rare but severe eye inflammatory disorder caused by bacterial infection that can occur after cataract surgery. Most bacteria are part of the patient’s natural flora, and even with antibiotic treatment, it causes considerable ocular morbidity and vision loss. Purpose To investigate the preoperative conjunctival flora and their antibiotic susceptibility in patients undergoing cataract surgery at Ibn Al-Haitham Teaching Eye Hospital, a tertiary ophthalmology center in Baghdad, Iraq. Methods This cross-sectional, single-center study based on conjunctival swabs of patients prior to cataract surgery and cultured using blood agar, chocolate agar, MacConkey agar, and Sabouraud agar. Bacterial isolates were identified using Gram staining and biochemical tests, and antibiotic sensitivity was determined using the disc diffusion method according to CLSI guidelines. Statistical analysis was done by SPSS Statistics Version 23. Results A total of 200 patients (200 conjunctival swabs of consecutive 200 eyes) scheduled for cataract surgery were included. Positive cultures were found in 45 (24%) patients. Coagulase-negative Staphylococcus epidermidis was the most frequently isolated microorganism (75% of isolates), followed by Staphylococcus aureus (14.58%), Aspergillus species (6.25%), and E. coli (4.17%). S. epidermidis showed the highest sensitivity to ofloxacin (97.2%) and chloramphenicol (94.4%) and the lowest sensitivity to fusidic acid (11.1%) and ceftazidime (5.6%). S. aureus exhibited the highest sensitivity to chloramphenicol (100%) and tobramycin (85.7%) but was completely resistant to ceftazidime and fusidic acid (100% resistance). E. coli isolates were 100% sensitive to ciprofloxacin, ofloxacin, and chloramphenicol. Conclusion The study revealed conjunctival microbial colonization in 24% of cataract surgery candidates, with S. epidermidis being the most prevalent isolate. Chloramphenicol, ofloxacin, Tobramycin, and Ciprofloxacin showed high sensitivity. Fusidic acid and Ceftazidime exhibited negligible sensitivity.